DIAGNOSIS AND COMPLEX TREATMENT OF SEAM’S LACK OF THE GASTROINTESTINAL TRACT OF PATIENTS WITH GASTRIC ULCER AND DUODENAL ULCER - D. M. Krasilnikov; M. M. Minnullin; Ya. U. Nikolaev (Креативная хирургия и онкология, 2017)
The causes of development of seam’s lack of the gastrointestinal tract of patients who underwent surgery because of complications of gastric ulcer and duodenal ulcer are studied. The classification of forms of seam’s lack of duodenal stump and gastroenteroanastomosis is presented. The new  approaches in diagnosis and  complex  treatment of  patients with seam’s lack of the gastrointestinal tract are offered.